GDE6 promotes progenitor identity in the vertebrate neural tube - McKean, Madeline; Napoli, Francesca R.; Hasan, Tahira; Joseph, Thea; Wheeler, Alison; Beebe, Katherine; Soriano-Cruz, Stephanie; Kawano, Minori; Cave, Clinton (Frontiers in Neuroscience, 2023)
The generation of neurons in the central nervous system is a complex, stepwise process necessitating the coordinated activity of mitotic progenitors known as radial glia. Following neural tube closure, radial glia undergo a period of active proliferation to rapidly expand their population, creating a densely packed neuroepithelium. Simultaneously, radial glia positioned across the neural tube are uniquely specified to produce diverse neuronal sub-types. Although these cellular dynamics are well studied, the molecular mechanisms governing them are poorly understood. The six-transmembrane Glycerophosphodiester Phosphodiesterase proteins (GDE2, GDE3, and GDE6) comprise a family of cell-surface enzymes expressed in the embryonic nervous system. GDE proteins can release Glycosylphosphatidylinsitol-anchored proteins from the cell surface via cleavage of their lipid anchor. GDE2 has established roles in motor neuron differentiation and oligodendrocyte maturation, and GDE3 regulates oligodendrocyte precursor cell proliferation. Here, we describe a role for GDE6 in early neural tube development. Using RNAscope, we show that Gde6 mRNA is expressed by ventricular zone progenitors in the caudal neural tube. Utilizing in-ovo electroporation, we show that GDE6 overexpression promotes neural tube hyperplasia and ectopic growths of the neuroepithelium. At later stages, electroporated embryos exhibit an expansion of the ventral patterning domains accompanied by reduced cross-repression. Ultimately, electroporated embryos fail to produce the full complement of post-mitotic motor neurons. Our findings indicate that GDE6 overexpression significantly affects radial glia function and positions GDE6 as a complementary factor to GDE2 during neurogenesis.